The Netherlands - van Hilvoorde, I. (Comparative elite sport development. Systems, structures and public policy, 2025)
The Netherlands is a relatively small, but prosperous and densely populated country (European Union, 2019; see also Levy & Herzog, 1974). It is the second densest country in the world. It usually ranks high among international indices such as freedom, human development, quality of life and happiness (Boelhouwer, 2002). The Dutch are known to have a rich sports culture and a good sports infrastructure (Hoekman, Breedveld & Kraaykamp, 2016). Of the nearly 18 million inhabitants, about 5 million inhabitants are members of one of the country's 25,000 sport clubs. Like every country, the Netherlands also has its own sports tradition, with sports that are practiced almost exclusively in the Netherlands, such as korfball, a mixed field sport that can be called folkloric, but still has almost 100,000 active players (Van Bottenburg & Vermeulen, 2011). This `century-old cousin of basketball` is a team sport that was devised for women and men to play together (Longman, 2023).